THE VIRGIN MARY AS LADY GRAMMAR IN THE MEDIEVAL WEST. (2019) - DONAVIN, GEORGIANA
Abstract : The Virgin Mary, as Mother of the Word, has long been associated with early literacy training in the medieval West, an association that, as this article argues, connects her to The Marriage of Philology and Mercury's Lady Grammar. While Gary P. Cestaro has demonstrated the ways in which representations of Lady Grammar became more maternal throughout the medieval period, this article demonstrates how and why the Virgin Mother took on the persona of Lady Grammar in both verbal and material arts from the High to the Late Middle Ages. It explores the famous sculptures of the Virgin and Lady Grammar on the Royal Portal at Chartres Cathedral, the writings of grammatical theorists that led to these depictions, and the thirteenth-century artes poetriae that portray Mary as a Christian Grammatica . From St. Augustine's declaration that grammar is a "guardian" to the claims of Gervais of Melkley, John of Garland, and Eberhard the German that Mary is the mother of beautiful expressions, grammatical thought and practice in the medieval West led to a characterization of the Virgin, guardian of the Word in her womb and parent to Wisdom, as the supreme teacher and exemplar of Latin. Adopting Lady Grammar's iconography of the nourishing breast, classroom text, and punitive whip, the Virgin Mary is not only connected to basic Latin instruction but also comes to embody its principles.